Moč imena - Lukács, István (Slavistična revija, 1999)
The study departs from onomastic studies by French and Russian experts from the 1950's on. The research of literary characters' names can be an autonomous method of the analysis of a literary work. in characters' names in Miroslav Krleža's and Ivan Cankar's work one finds almost identical dilemmas of the universal and the national. The common denominator of the two is Nietsche's philosophy. Unlike Krleža, Cankar did not subvert traditional romantic love, however, his libidinously enigmatic ludionysm indicate an attempt of this subversion.
Keywords: Cankar, Ivan, 1876-1918; hrvaška književnost; Krleža, Miroslav, 1893-1981; literarna teorija; literary theory; onomastics; onomastika; osebna imena; Slovene literature; slovenska književnost